PENGARUH LINGKUNGAN SOSIAL DAN PENDIDIKAN TERHADAP PRAKTIK MODERASI BERAGAMA - Lista Lista; Anitha Joice Randan, Mersiani Tanga (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2023)
This research is an in-depth qualitative study aimed at qualitatively analyzing and reviewing the literature on the influence of social and educational environments on the practice of religious moderation in society. The main focus of this research is to understand how social norms in the surrounding environment and individual educational experiences shape attitudes, understanding, and actions related to religious moderation. Using a qualitative approach, this study involves data collection through the analysis of participant narratives. The findings of this research present thematic insights that include the impact of social norms on attitudes toward religious moderation. Data analysis also highlights the role of education in shaping perceptions and practices of moderation by exploring the impact of the curriculum, teaching methods, and the role of teachers as key mediators. The conclusion of this research provides in-depth insights into the complexity of the interaction between social and educational environments in shaping the practice of religious moderation. Its implications include recommendations for improvements in the design of educational curricula and the expansion of social eflorts that support interfaith dialogue and tolerance in society. This research provides a foundation for a deeper understanding of how these factors are interconnected and influence the practice of religious moderation within the framework of social and educational contexts.